Contraception for adolescent and young adult women - Gilliam, Melissa; Whitaker, Amy (Springer New York, 2014)
Now more than ever there is a need for youth to learn about and use contraception consistently and effectively. Contraception for Adolescent and Young Adult Women is a valuable resource for gynecologists and primary care practitioners who are on the front lines when it comes to discussing, recommending, and prescribing contraceptive options to adolescent and young adult women. The book is filled with evidence-based information presented in an easy-to-access format, ideal for the busy clinician who needs information at his or her fingertips. The first chapter answers the question "why is contraception important in this population?" and outlines the basics of the initial clinical visit. The book continues by covering each method of contraception currently available, and concludes with a survey of special issues pertinent to young women. In its entirety, the content lays the groundwork for helping providers improve clinical practice in contraceptive care, tailored to the unique needs of young women. This book serves as an excellent reference for family physicians, adolescent medicine physicians, gynecologists, and anyone who wishes to learn and implement best contraceptive counseling and provision practices.